Mekanisme Pengupahan Melalui Sistem Bagi Hasil Prespektif Hukum Islam - Sainul Sainul (Institut Agama Islam Negeri Metro, 2021)
Upah adalah harga yang dibayarkan kepada pekerja atas jasanya dalam produksi kekayaan seperti faktor produksi lainnya, tenaga kerja diberikan imbalan atas jasanya, dengan kata lain upah adalah harga dari tenaga yang dibayar atas jasanya dalam produksi. Di dalam Islam upah disebut juga dengan ijarah, al-ijarah berasal dari kata al-ajru yang berarti menurut bahasanya ialah al-iwadh yang arti dalam bahasa Indonesianya ialah ganti dan upah, sedangkan ujroh yaitu upah untuk pekerja. Dalam penetapan upah dalam Islam upah pegawai pemerintah terkadang dipakai sebagai petunjuk untuk menetapkan upah buruh secara keseluruhan. Ternyata upah pegawai pemerintah sangat besar pengaruhnya terhadap seluruh tingkat upah dalam industri yang lain dalam Negara, penetapan upah dalam Islam diantaranya yaitu : upah disebutkan sebelum pekerjaan dimulai, membayar upah sebelum keringatnya kering. Pembahasan ini mengangkat fenomena dalam pemberian upah yang dilakukan para pemilik toko kepada karyawan. Tujuan penelitian ini adalah untuk mendeskripsikan dan menganalisis pengupahan pada toko – toko yang memiliki karyawan serta mendeskripsikan dan menganalisis sistem pengupahan ditinjau dengan sistem pengupahan hukum Islam. Wage is the price paid to workers for their services in the production of wealth like other factors of production, labor is rewarded for its services in production. In Islam, wages are also called ijarah, which comes from the word al-ajru, which means compensation and wages, while ujroh is wages for workers. In the setting of wages in Islam, the wages of government employees are sometimes used as a guide to determine the wages of workers as a whole. It turns out that the wages of government employees have a very large influence on all levels of wages in other industries in the country, the determination of wages in Islam include: wages are mentioned before work begins, pay wages before the sweat dries. This discussion raises the phenomenon in the provision of wages made by shop owners to employees. The purpose of this study is to describe and analyze wages in shops that have employees and to describe and analyze the wage system in terms of the Islamic law wage system. This discussion uses the method of describing or describing data that has been collected from a phenomenon that occurs. The results of this discussion are that the wages given by the shop owners to employees who are reviewed by Islamic law and the characteristics in the provision of wages in Islam are appropriate, including there is a contract in wages between shop owners and employees, in giving wages, wages are given after the work is completed and the existence of a work agreement between the two parties, there are Islamic values in wages, namely the value of justice and the value of feasibility.